Reductive Coupling of Diynes at Rhodium Gives Fluorescent Rhodacyclopentadienes or Phosphorescent Rhodium 2, 2'‐Biphenyl Complexes. Issue 30 (29th June 2016) - Sieck, Carolin; Tay, Meng Guan; Thibault, Marie‐Hélène; Edkins, Robert M.; Costuas, Karine; Halet, Jean‐François; Batsanov, Andrei S.; Haehnel, Martin; Edkins, Katharina; Lorbach, Andreas; Steffen, Andreas; Marder, Todd B.
Abstract: Reactions of [Rh( κ 2 ‐ O, O ‐acac)(PMe3 )2 ] (acac=acetylacetonato) and α, ω‐bis(arylbutadiynyl)alkanes afford two isomeric types of MC4 metallacycles with very different photophysical properties. As a result of a [2+2] reductive coupling at Rh, 2, 5‐bis(arylethynyl)rhodacyclopentadienes (A ) are formed, which display intense fluorescence ( Φ =0.07–0.54, τ =0.2–2.5 ns) despite the presence of the heavy metal atom. Rhodium biphenyl complexes (B ), which show exceptionally long‐lived (hundreds of μs) phosphorescence ( Φ =0.01–0.33) at room temperature in solution, have been isolated as a second isomer originating from an unusual [4+2] cycloaddition reaction and a subsequent β ‐H‐shift. We attribute the different photophysical properties of isomers A and B to a higher excited state density and a less stabilized T1 state in the biphenyl complexes B, allowing for more efficient intersystem crossing S1 →Tn and T1 →S0 . Control of the isomer distribution is achieved by modification of the bis‐ (diyne) linker length, providing a fundamentally new route to access photoactive metal biphenyl compounds. Abstract : The light at the end of the cycle : A combination of novel reactivity of bis‐ (diynes) at rhodium centers with the unusual photophysical properties of the two isomeric products formed is reported. Thus, reactions of alkyl‐linked bis‐(diynes) at Rh I give either fluorescent rhodacyclopentadienes via [2+2] coupling (normal reactivity, unusual photophysical behavior), or phosphorescent dibenzorhodacyclopentadienes via a [4+2] coupling (unusual reactivity, unexpectedly long‐lived luminescence in solution at room temperature).